Faktor-faktor yang berhubungan dengan pengetahuan dan sikap remaja terhadap HIV/AIDS: Analisa Data Sekunder Survei Demografi dan Kesehatan Indonesia (SDKI) 2017 - Purwanto, Edi; Cinta, Griselda Zahira (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Adolescents are residents aged 10–19 years. The number of Indonesian adolescents aged 10–19 years reaches around 43.5 million people, equivalent to 18% of the total population. It was recorded in 2014 that there were around 1.2 billion adolescents in the world, which also includes 18% of the global population. Adolescents are more vulnerable than adults to unplanned pregnancies, sexually transmitted diseases and HIV/AIDS. The level of adolescent knowledge about healthy lifestyles and information on various diseases is very minimal. In 2021, it was recorded that 650,000 people died from HIV, while around 1.5 million people were infected with the virus. To prevent the worst-case scenario, namely 7.7 million HIV-related deaths in the next ten years, a significant increase in prevention efforts is needed. Purpose: To determine factors related to adolescent knowledge and attitudes towards HIV/AIDS. Method: Quantitative research with cross-sectional design to analyze factors related to adolescent knowledge and attitudes towards HIV/AIDS. Information in this study refers to secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS). For analysis purposes, researchers combined three datasets, namely IDBR71FL (Birth Code), IDCR71FL (Couple Code), and IDHR71FL (Household Code) to find relevant variables. Based on the inclusion criteria with stratified random sampling technique, the number of samples used was 168 respondents. The collected data were analyzed using chi square. Results: The majority of respondents had high school education as many as 96 (57.1%), lived in urban areas as many as 117 respondents (69.6%), did not get knowledge about HIV/AIDS as many as 132 (78.6%), did not get information about HIV/AIDS as many as 119 (70.8%), and most respondents did not get HIV/AIDS School as many as 110 (65.5%). Based on the chi square test, the most dominant variable was age (p value = 0.000). Conclusion: There is an increase in adolescent knowledge and attitudes about HIV-AIDS through school-based education programs (HIV/AIDS Schools). Age factors have the most dominant influence on adolescent knowledge and attitudes towards HIV/AIDS. Suggestion: It is hoped that further researchers can conduct analysis and interventions with more specific factors to see the increase in adolescent knowledge and attitudes towards HIV/AIDS. Keywords: Adolescents; Attitude; HIV/AIDS; Knowledge. Pendahuluan: Remaja adalah penduduk dalam rentang usia 10–19 tahun. Jumlah remaja Indonesia dalam rentang usia 10–19 tahun mencapai sekitar 43.5 juta jiwa, setara dengan 18% dari total penduduk. Tercatat pada tahun 2014 bahwa terdapat sekitar 1.2 miliar remaja di dunia, yang juga mencakup 18% dari populasi global. Remaja lebih rentan daripada orang dewasa dari kehamilan yang tidak direncanakan, penyakit menular seksual dan HIV/AIDS. Tingkat pengetahuan remaja tentang pola hidup sehat dan informasi berbagai penyakit sangat minim. Pada tahun 2021, tercatat sebanyak 650.000 orang meninggal akibat HIV, sementara sekitar 1.5 juta orang terinfeksi virus tersebut. Untuk mencegah skenario terburuk, yakni terjadinya 7.7 juta kematian terkait HIV dalam sepuluh tahun ke depan, diperlukan peningkatan yang signifikan dalam upaya penanggulangan. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan pengetahuan dan sikap remaja terhadap HIV/AIDS. Metode: Penelitian kuantitatif dengan desain cross-sectional untuk menganalisis faktor yang berhubungan terhadap pengetahuan dan sikap remaja terhadap HIV/AIDS. Informasi dalam riset ini merujuk pada data sekunder dari Survei Demografi dan Kesehatan Indonesia (SDKI) tahun 2017. Bagi keperluan analisis, peneliti mengombinasikan tiga dataset yaitu IDBR71FL (Births Recode), IDCR71FL (Couples Recode), dan IDHR71FL (Household Recode) guna menemukan variabel yang relevan. Berdasarkan kriteria inklusi dengan teknik stratified random sampling, jumlah sampel yang digunakan sebanyak 168 responden. Data akumulasi dianalisis menggunakan chi square. Hasil: Mayoritas responden memiliki tingkat pendidikan SMA yaitu sebanyak 96 (57.1%), wilayah tempat tinggal di perkotaan sebanyak 117 responden (69.6%), tidak mendapatkan pengetahuan tentang HIV/AIDS sebanyak 132 (78.6%), tidak mendapatkan informasi tentang HIV/AIDS sebanyak 119 (70.8%), dan sebagian besar responden tidak mendapatkan HIV/AIDS School sebanyak 110 (65.5%). Berdasarkan uji chi square, variabel paling dominan adalah usia (p-value=0.000). Simpulan: Terdapat peningkatan pengetahuan dan sikap remaja tentang HIV-AIDS melalui program pendidikan berbasis sekolah (HIV/AIDS School). Faktor usia memiliki pengaruh paling dominan terhadap pengetahuan dan sikap remaja terhadap HIV/AIDS. Saran: Diharapkan peneliti selanjutnya dapat melakukan analisa dan intervensi dengan faktor yang lebih spesifik untuk melihat peningkatan pengetahuan dan sikap remaja terhadap HIV/AIDS. Kata Kunci: HIV/AIDS; Pengetahuan; Remaja; Sikap.